Studies on Tensile Strength, Fracture Surface and Biodegradation of Biocomposite from Polyvinyl Alcohol (PVA) Filled by Sugarcane Bagasse Fiber - Mochamad Asrofi; Reza Marinanda Fajar; Dwi Djumhariyanto; Salahuddin Junus; R. A. Ilyas; M. R. M. Asyraf; L Rajeshkumar (Green Engineering Society, 2023)
Synthetic plastic is a material that is difficult to decompose in the environment and causes serious problems in long term such as an increase in the volume of waste. To reduce plastic waste, biodegradable composite (biocomposite) is expected to overcome this problem. Natural cellulose fiber can be used as a filler in biopolymer matrix based biocomposite. This study aims to determine the tensile properties, fracture morphology, and biodegradation rate of biocomposite from Polyvinyl Alcohol (PVA) and sugarcane bagasse fiber. The test of biocomposite samples was carried out with a tensile test, scanning electron microscopy (SEM), and soil burial test. The results show that the highest tensile strength and modulus elasticity was in PVA pure film for 2.15 MPa and 3.468 MPa, respectively. The addition of cellulose fiber from sugarcane bagasse in the PVA matrix does not have a strengthening effect on the tensile strength of the biocomposite. This is due to the presence of porosity, agglomeration, and poor bonding between the matrix and fiber according to the SEM observation. The biodegradation rate showed that all biocomposite samples were degraded in the soil and had weight loss above 40% after 15 days of burial in the soil.